2018
DOI: 10.1007/s11356-018-1220-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemically and size-resolved particulate matter dry deposition on stone and surrogate surfaces inside and outside the low emission zone of Milan: application of a newly developed “Deposition Box”

Abstract: The collection of atmospheric particles on not-filtering substrates via dry deposition, and the subsequent study of the particle-induced material decay, is trivial due to the high number of variables simultaneously acting on the investigated surface. This work reports seasonally resolved data of chemical composition and size distribution of particulate matter deposed on stone and surrogate surfaces obtained using a new method, especially developed at this purpose. A "Deposition Box" was designed allowing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…In terms of PM deposition rates (DR, calculated as µg/cm 2 month −1 ), the values obtained in the present study for quartz filters are in agreement with those obtained for marble surfaces in a study recently carried out in Milan [17]: on average 68.9 µg/cm 2 month −1 for site 1 and 54.1 µg/cm 2 month −1 for site 2 against values in the range of about 50-70 µg/cm 2 month −1 measured in Milan for Carrara marble and quartz filters as surrogate surfaces [17] during the same period of the first exposure test (2014-2015).…”
Section: Cl/na K/nasupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of PM deposition rates (DR, calculated as µg/cm 2 month −1 ), the values obtained in the present study for quartz filters are in agreement with those obtained for marble surfaces in a study recently carried out in Milan [17]: on average 68.9 µg/cm 2 month −1 for site 1 and 54.1 µg/cm 2 month −1 for site 2 against values in the range of about 50-70 µg/cm 2 month −1 measured in Milan for Carrara marble and quartz filters as surrogate surfaces [17] during the same period of the first exposure test (2014-2015).…”
Section: Cl/na K/nasupporting
confidence: 92%
“…Such process was identified as an important decay mechanism of the façade in the past [33] and can be favored by the specific exposure conditions [2]. Furthermore, the higher sulphate/nitrate ratio found for the marble surfaces with respect to quartz filters is in accordance with what already observed in a previous study [17]. The overall characterization results indicate that the deposits have a significant potential for deterioration of the stone surfaces.…”
Section: Characterization Of Deposits On Marble and Surrogate Substratessupporting
confidence: 87%
See 1 more Smart Citation
“…In this case too, the signal of the eluent was decreased with a chemical suppressor (Dionex PTFE filters were chosen because they are among the most common membranes for aerosol collection, thanks to their low blank values for ions they are a suitable matrix for ion chromatography analysis [76] (Section 2.2); in addition, previous studies [8,18,19,77] demonstrated that hydrophobic supports are the most suitable for aerosol-water interaction measurements (e.g., via conductance measurements). In addition, their hydrophobicity makes them a good surrogate [66] for hydrophobic surfaces, e.g., epoxy-based composites that constitute PCBs and circuit component encapsulates [78] and for glass/ceramic insulator material, making them a good candidate for the present study. Quartz fiber filters were used to determined elemental and organic carbon as detailed in Section 2.2.…”
Section: Aerosol Chemical Characterizationmentioning
confidence: 99%
“…At this purpose, aerosol samples were collected on PTFE (Teflon) in different environments (urban and rural site), in Northern Italy (Po Valley). The investigated sites are located in the Po Valley, a hotspot for atmospheric pollution [65] where the dry aerosol deposition rate ranges from 30 to 70 µg cm −2 month −1 [66] making the aerosol a potential dangerous material for energy application. Moreover, the two urban and rural sites were chosen as affected by different EC and ionic content [67].…”
Section: Introductionmentioning
confidence: 99%